The complexes of neodimium bromide with carbamide and acetamide: synthesis and structure - L. Yu. Alikberova; D. V. Al’Bov; P. S. Kibal’Nikov; M. I. Vergeles; G. A. Fedorova; V. V. Kravchenko (Тонкие химические технологии, 2015)
New acetamide complexes of neodimium bromides Nd(Ur)6(H2O)2]Br3 (I) и [Nd(AA)4(H2O)4]Br3∙H2O (II) (Ur - carbamide; AA - acetamide) were synthesized. The resulting complexes were characterized by chemical analysis, infrared spectroscopy and X-ray diffraction method. It is shown that the coordination of the ligands (water molecules at inner sphere, carbamide and acetamide) by the neodimium atoms occurs through the oxygen atoms, and the coordination polyhedron is a distorted square antiprism (CN = 8). The bromide ions are not coordinated and are located in the outer sphere. The crystals of I contain complex cations [Nd(Ur)6(H2O)2]3+. The shape of the coordination polyhedron for the neodimium atom in I is the transition between the dodecahedron and a distorted tetragonal antiprisms. The shape of the coordination polyhedron for II is closest to the two-capped